Analisis Kesiapsiagaan K3 di Rumah Sakit Umum Daerah Cengkareng Dalam Upaya Penanggulangan Bencana Kebakaran - Ade Irma Seftyani Lubis; Salshabila Azzahra Sirait; Aldi Syahputra Nasution; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
Hospitals as a health service facility are part of the health resources that are very necessary to support the implementation of health efforts. The provision of health services in hospitals has very complex characteristics and organization. The danger of fire risk in hospital buildings originates from several activities or equipment in the hospital itself, such as the use of large capacity electrical equipment (radiology rooms), the use of high pressure gas cylinders and flammable and explosive chemicals. This research aims to analyze hospital preparedness in efforts to deal with fire disasters at Cengkareng Regional Hospital. This research uses a literature review method, the data is collected from previous studies. Results: From observations from previous research and from the Cengkareng Regional Hospital's emergency response guide. Cengkareng Regional Hospital has carried out appropriate disaster management efforts. Both natural disasters and disasters caused by humans. In carrying out fire disaster management efforts, the hospital has prepared an emergency response organizational structure in a very neat and wise manner, and is supported by preventive equipment that is very complete in terms of type and quantity. The equipment is also in good condition.